Madame Choi and the monsters - Spät, Patrick (SelfMadeHero, 2024)
"Kidnapped by North Korean secret agents, at the orders of the country's future leader Kim Jong-il, the South Korean film star Choi Eun-hee finds herself having to give the performance of her life. Held against her will for five years, a bird in a gilded cage, Madame Choi is joined by her ex-husband, the film director Shin Sang-ok, and all is then revealed: their joint abduction has been orchestrated by the movie-mad heir-apparent in a bizarre bid to revitalize the North Korean film industry. Under constant surveillance, the reunited couple is coerced into make a series of big-budget films, including a North Korean version of Godzilla--based on the legend of Bulgasari, a monster of insatiable appetite--while themselves plotting to escape the clutches of their monstrous dictator with a set of covert tape recordings of their own"--Page 4 of cover.